2006
DOI: 10.1007/s10800-006-9133-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sorbitol on zinc film deposition, zinc dissolution process and morphology of deposits obtained from alkaline bath

Abstract: A novel cyanide-free zinc deposition bath was developed in which sorbitol was added at various concentrations. Voltammetric studies indicated that the reduction process is influenced thermodynamically and kinetically by the sorbitol concentration. Also, two cathodic processes were observed, one (wave) associated with the hydrogen evolution reaction (HER) on 1010 steel, the other (peak) with zinc bulk reduction, simultaneous to the HER. Furthermore, the plating-process kinetics was controlled by mass transport.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 9 publications
3
31
0
6
Order By: Relevance
“…3c), a peak a 1 is seen in the positive sweep at -1.48 V and -1.43 V, in the absence and presence of 0.20 M mannitol, respectively, which is due to zinc dissolution. Thus, mannitol appears to hinder zinc dissolution, probably by being adsorbed on the zinc electrodeposit, corroborating earlier results of Carlos and co-workers [11], who reported that zinc dissolution was inhibited in the presence of sorbitol.…”
Section: Methodssupporting
confidence: 89%
See 3 more Smart Citations
“…3c), a peak a 1 is seen in the positive sweep at -1.48 V and -1.43 V, in the absence and presence of 0.20 M mannitol, respectively, which is due to zinc dissolution. Thus, mannitol appears to hinder zinc dissolution, probably by being adsorbed on the zinc electrodeposit, corroborating earlier results of Carlos and co-workers [11], who reported that zinc dissolution was inhibited in the presence of sorbitol.…”
Section: Methodssupporting
confidence: 89%
“…Zinc has been electrodeposited from various alkaline solutions including zincate without additives [4] or with additives such as the following: C 6 F 13 C 2 H 4 (OC 2 H 4 ) 12 OH and C 12 H 25 (C 2 H 4 O) 12 H [5]; a tetraalkylammonium salt [6,7]; ammine-oxalate-EDTA [8]; tetramethylammonium, tetrabutylammonium or benzyl alcohol [9]; glycerol [10], and sorbitol [11]. Alkaline electrolytes are preferable not only from the point of view of environmental protection but also for their low corrosiveness, compared to acid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be inferred from these curves that this complex hinders zinc dissolution, since the anodic peak potential was shifted *50 mV in the positive direction in the presence of boricsorbitol complex. This result corroborates those obtained by Pereira et al [26] who report that Zn electrode Similar results were obtained at different E f (-1.35 V and -1.55 V). Also, it was noted that the voltammetric dissolution of zinc film produced in a plating bath containing glycerol was similar to that in the absence of additive (Fig.…”
Section: Study Of Deposition Process In the Presence Of Polyalcoholssupporting
confidence: 93%